2001
DOI: 10.1210/jc.86.10.4657
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of 5 Years of GH Replacement Therapy in GH-Deficient Adults: Sustained Effects on Body Composition, Bone Mass, and Metabolic Indices

Abstract: GH replacement therapy has proved its efficacy and safety in short-term trials and in a few long-term trials with limited number of subjects. In this 1-center study, including 118 consecutive adults (70 men and 48 women; mean age, 49.3 yr; range, 22-74 yr) with adult-onset GH deficiency, the effects of 5 yr of GH replacement on body composition, bone mass, and metabolic indices were determined. The mean initial GH dose was 0.98 mg/d. The dose was gradually lowered, and after 5 yr the mean dose was 0.48 mg/d. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
109
6
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 0 publications
21
109
6
4
Order By: Relevance
“…While this is in keeping with the literature [21], this study additionally showed that in the Japanese patients the loss of FM specifically affects the trunk. The decrease in percent trunk fat mass at 48 weeks would correspond to an average loss of about 1.0 kg in abdominal FM.…”
Section: Discussionsupporting
confidence: 92%
“…While this is in keeping with the literature [21], this study additionally showed that in the Japanese patients the loss of FM specifically affects the trunk. The decrease in percent trunk fat mass at 48 weeks would correspond to an average loss of about 1.0 kg in abdominal FM.…”
Section: Discussionsupporting
confidence: 92%
“…[49][50][51][52][53][54][55][56][57][58][59][60] In addition to poor QoL, both GHD and hypogonadism can contribute to decreased lean body mass, increased fat mass (in particular, visceral fat), and poor exercise capacity that further contribute to poor QoL, obesity, and MetS, increasing cardiovascular disease (CVD) risk. 51,54,57,[61][62][63][64][65][66][67][68][69][70] Studies have shown that MetS is associated with, and predicts the development of, low serum testosterone levels in men. 62,64,65,71 Five of 6 subjects with hypogonadism had MetS and obesity.…”
Section: Previous Studies On Postconcussive Hypopituitarismmentioning
confidence: 99%
“…O GH estimula a hidroxilação renal da 25-OH vit D3, absorção renal de cálcio e tem efeitos renais de retenção de fosfato (2,43). Outro provável mecanismo de ação do GH é através de aumento na carga mecânica imposta aos ossos, visto que o GH leva a maior massa e força muscular (5,44). Uma correlação entre DMO e secreção de GH em adultos jovens saudáveis já foi descrita (45), bem como correlação entre níveis baixos de IGF-1 e risco de fraturas osteoporóticas em mulheres saudáveis pós-menopausa (46).…”
Section: Deficiência De Gh Em Adultos: Estudo Brasileirounclassified
“…Estudos com uso de GH a longo prazo (pelo menos 18-24 meses) mostram aumento na DMO, mas ainda não se sabe se isso se traduz em uma redução no risco de fraturas (5,(49)(50)(51)(52)(53)(54). Encontramos aumento da DMO de coluna lombar e fêmur após 12 meses de reposição de GH (1,99±4,27% em coluna lombar e 2,55±4,30% no fêmur), que se manteve após 24 meses de tratamento (2,31±7,17% em coluna lombar e 5,33±9,64% no fêmur).…”
Section: Deficiência De Gh Em Adultos: Estudo Brasileirounclassified
See 1 more Smart Citation